Association of E‐cadherin methylation with risk of nasopharyngeal cancer: A meta‐analysis. Issue 11 (26th June 2018) - Wu, Cheng; Peng, Shan; Sun, Wei; Luo, Min; Su, Beibei; Liu, Dongbo; Hu, Guoqing
Abstract: Background: Various studies have assessed the association between E‐cadherin methylation and risk of nasopharyngeal cancer (NPC) but the conclusion remains unclear. This meta‐analysis was conducted to evaluate the effects of E‐cadherin methylation on the incidence and clinicopathological characteristics of NPC. Methods: Ten studies published up to June 30, 2016, were collected. Odds ratios (ORs) with corresponding confidence intervals (CIs) were calculated and summarized, respectively. Results: The E‐cadherin methylation in NPC was significantly higher than those in normal groups (OR 16.23; 95% CI 8.34‐31.60; P < .001). Ethnicity‐stratified analysis indicated that E‐cadherin methylation was strongly correlated with NPC among both Asians (OR 16.98; 95% CI 8.45‐34.14; P < .001) and North Africans (OR 10.67; 95% CI 1.21‐93.72; P = .033). However, further analysis showed that E‐cadherin methylation was not strongly associated with clinicopathological feathers in patients with NPC. Conclusion: The E‐cadherin methylation is strongly associated with the incidence of NPC, which can serve as an effective biomarker for early detection of NPC.